MANDIBULAR INJURIES AND FRACTURES (International Conference on Economics, Finance, Banking and Management, 2025)
This article provides a comprehensive overview of mandibular fractures, which are among the most common facial bone injuries. Unlike nasal fractures, mandibular fractures often require surgical intervention due to the complex anatomy and essential function of the mandible. The discussion covers the etiology, epidemiology, pathophysiology, classification, and prognosis of mandibular fractures. Trauma—including motor vehicle accidents, interpersonal violence, and sports injuries—is the leading cause. The mandible’s unique ring-like structure often results in multiple fracture sites. Evaluation of associated injuries (e.g., cervical spine and traumatic brain injuries) is critical. Despite a relatively high perioperative complication rate, long-term outcomes are generally favorable. Smoking and alcohol use are noted as key risk factors for postoperative complications.